Regulation of Bacterial Manganese Homeostasis and Usage During Stress Responses and Pathogenesis - Martin, Julia E.; Waters, Lauren S. (Frontiers in Molecular Biosciences, 2022)
Manganese (Mn) plays a multifaceted role in the survival of pathogenic and symbiotic bacteria in eukaryotic hosts, and it is also important for free-living bacteria to grow in stressful environments. Previous research has uncovered components of the bacterial Mn homeostasis systems that control intracellular Mn levels, many of which are important for virulence. Multiple studies have also identified proteins that use Mn once it is inside the cell, including Mn-specific enzymes and enzymes transiently loaded with Mn for protection during oxidative stress. Emerging evidence continues to reveal proteins involved in maintaining Mn homeostasis, as well as enzymes that can bind Mn. For some of these enzymes, Mn serves as an essential cofactor. For other enzymes, mismetallation with Mn can lead to inactivation or poor activity. Some enzymes may even potentially be regulated by differential metallation with Mn or zinc (Zn). This review focuses on new developments in regulatory mechanisms that affect Mn homeostasis and usage, additional players in Mn import that increase bacterial survival during pathogenesis, and the interplay between Mn and other metals during Mn-responsive physiological processes. Lastly, we highlight lessons learned from fundamental research that are now being applied to bacterial interactions within larger microbial communities or eukaryotic hosts.